Exploring pre-service teachers’ inquisitiveness in contradictory mathematics problems - Hadi, Fida Rahmantika; Nusantara, Toto; Mahanal, Susriyati; Kuswandi, Dedi (Edelweiss Applied Science and Technology, 2025)
This research aims to analyze the inquisitiveness of critical thinking students in solving mathematical problems with contradictory information. The subjects in this study were 26 students who completed the test with contradictory mathematics problems, and then 2 students who exhibited inquisitiveness were selected for interviews. The data collection instruments used were tests and interviews. The data analysis techniques employed included data reduction, data presentation, and drawing conclusions. The results of this research show that there are students who demonstrate inquisitiveness. This is evidenced by the results of the subjects' answers, which meet the indicators of inquisitiveness. Some indicators of inquisitiveness that were met include asking questions and seeking information to find alternative answers. It can be concluded that the inquisitiveness of prospective teacher students aligns with the indicators by asking questions. The originality of prospective teachers' inquisitiveness becomes particularly evident when they confront contradictory mathematics problems, as their ability to question assumptions and explore unconventional solutions is crucial for developing innovative teaching strategies and fostering a deep mathematical understanding.